Developing tree volume equation for Parkia timoriana grown in home gardens and shifting cultivation areas of North-East India. Issue 4 (2nd October 2019) - Thangjam, Uttam; Sahoo, Uttam Kumar; Thong, Pentile; Sileshi, Gudeta W
ABSTRACT: Parkia timoriana (DC.) Merr. is an economically important agroforestry tree species grown in home gardens and shifting cultivation areas throughout the North-eastern states of India. This study aimed to establish a best fit volume model to facilitate estimation of biomass and carbon stock of the species without destructive sampling. Stem volumes of 360 trees representing 12 populations were estimated, and the data were used to develop 19 volume models involving diameter at breast height (D) and height (H). These models were then subjected to statistical test, and then cross-validated to select the best fitting model. The coefficient of determination (R 2 ), root mean square error (RMSE), mean absolute deviation (MAD) and Akaike's Information Criterion (AIC) were used for model selection, and scattered plot with residuals along with paired t-test were used for validation of the resultant models. Among the models compared, V = 0.12500–2.40265D + 21.43248D 2 was found to be the best using single independent variable (D), while V = 0.03177 + 1.032D 2 H was the best model among the models with two independent variables (D and H). These two models gave high accuracy and hence can be used for future referencing.